THE INFLUENCE OF INTERNET OF THINGS (IOT) ON DIGITAL MARKETING STRATEGY - Silvia Ekasari (CV. Adiba Aisha Amira, 2025)
The Internet of Things (IoT) has been a technological innovation that has had a significant impact on digital marketing strategies. IoT enables the collection of more complex consumer data through connected devices, creating opportunities for personalisation and optimisation of marketing campaigns. With more in-depth data analysis, companies can devise more relevant and effective strategies to increase customer engagement and loyalty. In addition, IoT strengthens the consumer experience through location-based promotions and real-time interactions, providing added value in building brand relationships. However, IoT deployment also presents challenges related to data protection and user privacy, which require serious attention from companies. With proper management, IoT offers tremendous potential to transform the digital marketing landscape to become more responsive and data-driven.